2020
DOI: 10.1007/s00417-020-04914-2
|View full text |Cite|
|
Sign up to set email alerts
|

Sub-clinical thickening of the fovea in diabetes and its relationship to glycaemic control: a study using swept-source optical coherence tomography

Abstract: Background Accumulation of multiple pockets of fluid at the fovea, as a complication of poor blood glucose control in diabetes, causes impairment of central vision. A new ability to demonstrate a pre-clinical phase of this maculopathy could be valuable, enabling diabetic individuals to be alerted to the need to improve their glycaemic control. This study aimed to use swept-source optical coherence tomography (SS-OCT) to measure foveal thickness and macular volume in diabetic individuals without cystoid macular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Test results were expressed as the percentage of total hemoglobin that was glycosylated in the sample. The method by which the A 1c Now®+ System assesses HbA 1c level has been described previously 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Test results were expressed as the percentage of total hemoglobin that was glycosylated in the sample. The method by which the A 1c Now®+ System assesses HbA 1c level has been described previously 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zafar et al 48 showed that, per unit increase in percent HbA1c from 7076 participants with diabetes, the RNFL thickness in the inferior quadrant correspondingly decreased. Furthermore, subclinical thickening of the retina is positively associated with HbA1c levels, 51 indicating retinal edema/neurodegeneration in response to hyperglycemia. Thus, to minimize the confounding effect of hyperglycemia, we adjusted for HbA1c in our models.…”
Section: Discussionmentioning
confidence: 99%